Recuperação Inteligente de Letras de Músicas na Web - Ribeiro, Rafael; Silla, Carlos (Proceedings of the SBC Undergraduate Research Contest (CTIC-SBC), 2014)
The task of automatic retrieval and extraction of lyrics from the web is of great importance to different Music Information Retrieval applications. Most of the existing approaches to deal with this problem rely on computation resources that often unavailable for songs which are not mainstream (usually English) songs. In this paper we present the Ethnic Lyrics Fetcher (ELF), a tool for Music Information Researchers, which has a novel lyrics extraction mechanism. To assess ELF Two experiments were performed. In the first, the novel lyrics extraction mechanism against 12 websites that have their lyrics in a well defined structure and, in addition, a comparison was made with the lyrics extraction method presented in [Geleijnse and Korst 2006]. The second experiment evaluated the performance of the ELF (Ethnic Lyrics Fetcher) as a tool for retrieving lyrics from the web. Our results show that ELF is a useful tool for users and researchers in Music Information Retrieval.